2011
DOI: 10.1007/s10238-011-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple immunoassay systems are negatively interfered by circulating cardiac troponin I autoantibodies

Abstract: Circulating cardiac troponin I (cTnI) autoantibodies have recently been detected in more and more patients with myocardial injury. In the present study, a total of 121 patients with acute myocardial infarction (AMI) were screened for cTnI autoantibodies using an indirect ELISA. Positive results were further confirmed by Western blot analysis. As a result, 13 autoantibody-positive sera were identified, in which cTnI values detected by different immunoassay systems are very different. Further evaluation revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…Circulating troponin autoantibodies are not rare, having been identified in 2%-20% of individuals, with or without cardiac disease, in various studies [20][21][22][23][24]. They may be directed towards cTnI [19,22] or cardiac troponin T [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating troponin autoantibodies are not rare, having been identified in 2%-20% of individuals, with or without cardiac disease, in various studies [20][21][22][23][24]. They may be directed towards cTnI [19,22] or cardiac troponin T [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, autoantibodies to cTnI have caused negative interference in some cTnI immunoassays [24,25]. Investigation of the epitope specificity of cTnI autoantibodies has shown that the cTnI midfragment (amino acids 30-100) is the commonest target of these antibodies [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies assessed anti-troponin I antibodies (9,12,14,(39)(40)(41)(42)(45)(46)(47)(48)50,51,(53)(54)(55)(56)(57)(58), whereas anti-troponin T antibodies were assessed in only 16% (n=1,636) of individuals (11,43,44,49,52) (including 993 individuals where both types of autoantibodies were evaluated) (11,44,49).…”
Section: Resultsmentioning
confidence: 99%
“…Over half of the studies included assessed individuals with cardiovascular diseases (9,11,12,14,39,40,(44)(45)(46)(47)(48)50,51,53,(55)(56)(57), especially DCM. The prevalence of anti-troponin I autoantibodies in DCM ranged from 7.0% (11) to 22.2% (in patients prior to immunoadsorption, notably decreased to 3.7% after immunoadsorption) (53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation